Analisis Keberhasilan Program Lembaga Keuangan Mikro dalam Mendukung UMKM di Medan - Amelia, Dinda; Saqina Nasution, Putri Amalia; Putri, Sella Permana; Junior Barus, Tony; Hayati, Fitri (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to analyze the effectiveness of Microfinance Institution (MFI) programs in supporting the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Medan City. A qualitative approach is used to deeply explore the contribution of MFIs in providing inclusive financial access, such as low-interest loans, term savings, and business management training. The results show that MFIs have a strategic role in overcoming capital constraints and increasing MSME productivity. However, challenges such as limited operational capital, credit risk, and complex policies are significant barriers. This study recommends strengthening access to capital through collaboration with formal financial institutions and simplifying regulations to improve the effectiveness of MFI services. The findings contribute to strengthening the role of MFIs as strategic partners in empowering MSMEs to support sustainable regional economic growth.